PWE-076 Continued biennial screening of faecal occult blood test (FOBT) positive and screening colonoscopy negative cohort in English bowel cancer screening programme—is it necessary?. (28th May 2012) - Majumdar, D; Patnick, J; Nickerson, C; Rutter, M D
Abstract : Introduction: The English NHS Bowel Cancer Screening Programme (BCSP) uses guaiac based faecal occult blood test (FOBT) as the screening tool, with people with a positive result undergoing colonoscopy. Subjects with adenomas who are in the low risk category and those with no adenomas at colonoscopy are invited to participate in the next gFOBT round in 2 years. This study evaluates the PPV of a second FOBT diagnostic colonoscopy following a second FOBT positive result. Methods: Data on each patient entering the NHS BCSP programme is prospectively recorded on the national BCSP database. The database was interrogated to identify subjects who had had a second FOBT positive diagnostic colonoscopy in BCSP 2 years after their first screening colonoscopy. The diagnostic colonoscopy PPV of this second FOB positive procedure was compared with the published PPV of first FOB positive diagnostic colonoscopies. 1 Results: The database was interrogated in April 2011. A total of 772 subjects were identified. The positive predictive value (PPV) for all colorectal neoplasia was 25.7% (n=199) and 0.9% (n=7) for colorectal cancer (CRC). 41.5% had a normal colonoscopy and 32.8% had non-neoplastic pathology. This compares with a PPV for CRC at the first FOB positive diagnostic colonoscopy of 10.1% and for all neoplasia of 53%. 2 Findings are summarised in the Abstract PWE-076 table 1 below. Out of the seven cancers three were Dukes' C, 2 Dukes' B and 2 Dukes' A stage. The sizes of the cancers ranged from 20 mm to 60 mm. Three were located in the rectum, three at the recto-sigmoid junction and one in the caecum. Conclusion: There is significant reduction of CRC and adenoma in the population undergoing a second FOBT positive colonoscopy compared to the first one (0.9% vs 10.1%, p value <0.0001 for CRC). Though the numbers are small, in the cohort where cancer is detected, presence of locally advanced cancer raises the question of missed lesion during the colonoscopy after first positive FOBT and therefore the current practise of biennial FOBT screening for this group is justified. Competing interests: None declared. Reference: 1. Logan R, Patnick J, Nickerson C, et al. Outcome of the Bowel Cancer Screening Programe in England after the first 1 million tests. Gut . Published Online First: 7 December 2011. doi:10.1136/gutjnl-2011-300843